Implementation Of Activity Based Costing On The Rate Of Inspired Services For Covid-19 Patients At Pusri Hospital, Palembang City - Belinda Syawaliyyah; Alwi Alwi (UNIVED Press, 2024)
This study aims to determine: (1) The cost calculation used by the hospital. Pu sri Palembang to determine the tariff for inpatient services for covid-19 patients in 2021, (2) Calculation of the Activity Based Costing System to determine the rate for inpatient services for COVID-19 patients at the hospital. Pusri Palembang in 2021, (3) Comparison of the calculation of the cost of inpatient services for Covid-19 patients based on hospital calculations with calculations using the Acitvity Based Costing System in 2021. The research method used is descriptive analysis method. The data collection method used in this research is to use the interview method and the documentation method. The interview method was used to obtain supporting data for writing, as for the list of questions as follows: How is the calculation of the cost method used by the hospital. Pusri Palembang to determine the tariff for inpatient services for Covid-19 patients in 2021?. The documentation method is used to obtain data on the list of rates for inpatient services for COVID-19 patients, hospitalization costs, and length of days of hospitalized patients. Based on the results of the study showed that: (1) The method applied by RS. Pusri Palembang to determine the tariff for inpatient services for COVID-19 patients at a rate of Rp. 2,473,606.50 (2) The tariff for inpatient services for Covid-19 patients using the Activity Based Costing method provides cheaper results. The difference that occurs is due to the imposition of overhead costs on each product. In the unit cost method, the overhead costs for each product are charged to only one cost driver, namely the number of days of hospitalization. Activity Based Costing is able to allocate activity costs to each product appropriately based on the consumption of each activity